2021
DOI: 10.1007/s13178-021-00538-1
|View full text |Cite
|
Sign up to set email alerts
|

Online Sexual Activities in Italian Older Adults: The Role of Gender, Sexual Orientation, and Permissiveness

Abstract: Introduction Online sexual activities (OSAs) are sexual behaviors involving online sexual content and stimuli and are categorized into non-arousal (N-OSAs), solitary arousal (S-OSAs), and partnered arousal activities (P-OSAs). As such activities in older age remain largely underexamined, this study aimed to explore OSAs in a sample of Italian older adults, analyzing their associations with gender and sexual orientation, considering sexual permissiveness as a moderator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 100 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…In line with this hypothesis, Daneback et al (2005) found that the use of chats or webcams for sexual purposes steadily increased with age in women, but not in men: in women, this OSA reached its peak prevalence (37%) between 35-49 years old, whereas in men, peak prevalence (38%) was observed at an earlier age (between 18-28 years old). Finally, the use of the Internet to look for sexual education (i.e., non-arousal activity) across the lifespan seems to follow an inverted U-shape: in people between 12-24 years old, age is a positive predictor of online sexual information seeking (i.e., youth are more likely to search for sexual information online as they get older) (Nikkelen et al, 2020); however, the prevalence of this OSA tend to decline after this age, especially in older people (Scandurra et al, 2021).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In line with this hypothesis, Daneback et al (2005) found that the use of chats or webcams for sexual purposes steadily increased with age in women, but not in men: in women, this OSA reached its peak prevalence (37%) between 35-49 years old, whereas in men, peak prevalence (38%) was observed at an earlier age (between 18-28 years old). Finally, the use of the Internet to look for sexual education (i.e., non-arousal activity) across the lifespan seems to follow an inverted U-shape: in people between 12-24 years old, age is a positive predictor of online sexual information seeking (i.e., youth are more likely to search for sexual information online as they get older) (Nikkelen et al, 2020); however, the prevalence of this OSA tend to decline after this age, especially in older people (Scandurra et al, 2021).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Moreover, the growing group of older adults exploring the possibilities the digital world offers for sex and love is another significant user segment. A recent study revealed that the online activities among older adults can be categorized into three groups: non-arousal activities (e.g., visiting educational websites or chatting on dating platforms), solitary arousal activities (e.g., watching pornography), and partnered arousal activities which involve at least one other individual (e.g., engaging in webcam sex) [54,55]. Hence, older adults are utilizing the digital space in the domains that align with application areas discussed in this work.…”
Section: Diverse (And Inclusive) Perspective On Sexualized Interactio...mentioning
confidence: 99%
“…Recent studies conducted in United States (Lentz & Zaikman, 2021;Leri & DelPriore, 2021) and Portugal (Silva et al, 2021) examining the effect of sexual orientation on sexual attitudes in women from the general population and young adults show that nonheterosexual women have more permissive sexual attitudes than heterosexual women. However, in Italy Scandurra et al (2022) explored the link between sexual orientation and sexual attitudes in men and women aged over 50 years and found no statistically significant relationship. In contrast, other studies in United States (Grollman, 2017;Nurius, 1983) and England (Swami et al, 2017) with both men and women samples found that non-heterosexuals have more liberal/erotophilic sexual attitudes than heterosexuals.…”
Section: Introductionmentioning
confidence: 98%
“…The main reason sexual attitudes have received so much attention is their relationship with sexual health (e.g., Carvalho et al, 2013;Sanders et al, 2006;Sierra et al, 2021) and sexual activity (e.g., Blanc et al, 2018b;Lemer et al, 2013). On the one hand, people with positive attitudes toward sexuality tend to report more permissive/liberal/erotophilic sexual attitudes than women (e.g., Ojedokun & Balogun, 2008;Ojo, 2014;Scandurra et al, 2022;Sprecher, 2013;Swami et al, 2017;Zuo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%